An analysis of fast photochemistry over high northern latitudes during spring and summer using in-situ observations from ARCTAS and TOPSE - Olson, J. R.; Crawford, J. H.; Brune, W.; Mao, J.; Ren, X.; Fried, A.; Anderson, B.; Apel, E.; Beaver, M.; Blake, D.; Chen, G.; Crounse, J.; et al. (Atmospheric Chemistry and Physics, 2012)
Observations of chemical constituents and meteorological quantities obtained during the two Arctic phases of the airborne campaign ARCTAS (Arctic Research of the Composition of the Troposphere from Aircraft and Satellites) are analyzed using an observationally constrained steady state box model. Measurements of OH and HO2 from the Penn State ATHOS instrument are compared to model predictions. Forty percent of OH measurements below 2 km are at the limit of detection during the spring phase (ARCTAS-A). While the median observed-to-calculated ratio is near one, both the scatter of observations and the model uncertainty for OH are at the magnitude of ambient values. During the summer phase (ARCTAS-B), model predictions of OH are biased low relative to observations and demonstrate a high sensitivity to the level of uncertainty in NO observations. Predictions of HO2 using observed CH2O and H2O2 as model constraints are up to a factor of two larger than observed. A temperature-dependent terminal loss rate of HO2 to aerosol recently proposed in the literature is shown to be insufficient to reconcile these differences. A comparison of ARCTAS-A to the high latitude springtime portion of the 2000 TOPSE campaign (Tropospheric Ozone Production about the Spring Equinox) shows similar meteorological and chemical environments with the exception of peroxides; observations of H2O2 during ARCTAS-A were 2.5 to 3 times larger than those during TOPSE. The cause of this difference in peroxides remains unresolved and has important implications for the Arctic HOx budget. Unconstrained model predictions for both phases indicate photochemistry alone is unable to simultaneously sustain observed levels of CH2O and H2O2; however when the model is constrained with observed CH2O, H2O2 predictions from a range of rainout parameterizations bracket its observations. A mechanism suitable to explain observed concentrations of CH2O is uncertain. Free tropospheric observations of acetaldehyde (CH3CHO) are 2–3 times larger than its predictions, though constraint of the model to those observations is sufficient to account for less than half of the deficit in predicted CH2O. The box model calculates gross O3 formation during spring to maximize from 1–4 km at 0.8 ppbv d−1, in agreement with estimates from TOPSE, and a gross production of 2–4 ppbv d−1 in the boundary layer and upper troposphere during summer. Use of the lower observed levels of HO2 in place of model predictions decreases the gross production by 25–50%. Net O3 production is near zero throughout the ARCTAS-A troposphere, and is 1–2 ppbv in the boundary layer and upper altitudes during ARCTAS-B.